2013
DOI: 10.1007/s10072-013-1440-7
|View full text |Cite
|
Sign up to set email alerts
|

Pain and thyroid hormones

Abstract: The role of endocrine systems in chronic pain mechanisms is slowly getting increasing experimental and clinical consideration. Many painful conditions appear to be directly and/or indirectly induced, reduced or, in some cases, modulated by hormones. We have done much work in trying to understand the relationship between hormones and pain, with particular attention to the hypothalamus-pituitary-gonadal axis. To expand our knowledge of this field, we have directed our attention to another axis, the hypothalamus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Indicatively, it has been observed that thyroid autoimmunity is facilitated by single nucleotide polymorphisms in genes regulating the immune system, such as human leukocyte antigen genes, cytokines genes, and thyroid specific genes, while polymorphisms in some of these genes have also been implicated in migraine pathogenesis . Furthermore, recent studies have shown that thyroid hormones are involved in pain mechanisms with TSH receptors being expressed in the cortical neurons and cerebral vasculature . There are several mechanisms that may explain how migraine could be a risk factor for hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Indicatively, it has been observed that thyroid autoimmunity is facilitated by single nucleotide polymorphisms in genes regulating the immune system, such as human leukocyte antigen genes, cytokines genes, and thyroid specific genes, while polymorphisms in some of these genes have also been implicated in migraine pathogenesis . Furthermore, recent studies have shown that thyroid hormones are involved in pain mechanisms with TSH receptors being expressed in the cortical neurons and cerebral vasculature . There are several mechanisms that may explain how migraine could be a risk factor for hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies explained the comorbidity by involvement of thyroid hormone in pain mechanisms with thyrotropin stimulating hormone receptors being expressed in the cortical neurons and cerebral vasculature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports can be found in the literature concerning thyroid hormones and their functions; however, studies of their connection with pain are scarce. The thyroid gland has a prominent role in tissue metabolism and development; in addition, the hypothalamic-pituitary-thyroid axis is central to the modulation and neurotransmission processes in the central nervous system [ 17 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Aloisi et al [ 17 ] , in a pilot study with a group of 200 women with chronic pain - whose medical history was investigated - found that 19% of them had some degree of thyroid dysfunction. That rate is similar to the overall value of 16.3% found in our analysis.…”
Section: Discussionmentioning
confidence: 99%